Vacuolar H+-Pyrophosphatase and Cytosolic Soluble Pyrophosphatases Cooperatively Regulate Pyrophosphate Levels in Arabidopsis thaliana. Issue 5 (24th April 2018) - Segami, Shoji; Tomoyama, Takaaki; Sakamoto, Shingo; Gunji, Shizuka; Fukuda, Mayu; Kinoshita, Satoru; Mitsuda, Nobutaka; Ferjani, Ali; Maeshima, Masayoshi
Abstract : Vacuolar H + -pyrophosphatase and cytosolic soluble pyrophosphatases play the leading and supportive role, respectively, in PPi homeostasis in Arabidopsis. Abstract: Inorganic pyrophosphate (PPi) is a phosphate donor and energy source. Many metabolic reactions that generate PPi are suppressed by high levels of PPi. Here, we investigated how proper levels of cytosolic PPi are maintained, focusing on soluble pyrophosphatases (AtPPa1 to AtPPa5; hereafter PPa1 to PPa5) and vacuolar H + -pyrophosphatase (H + -PPase, AtVHP1/FUGU5) in Arabidopsis thaliana . In planta, five PPa isozymes tagged with GFP were detected in the cytosol and nuclei. Immunochemical analyses revealed a high abundance of PPa1 and the absence of PPa3 in vegetative tissue. In addition, the heterologous expression of each PPa restored growth in a soluble PPase-defective yeast strain. Although the quadruple knockout mutant plant ppa1 ppa2 ppa4 ppa5 showed no obvious phenotypes, H + -PPase and PPa1 double mutants ( fugu5 ppa1 ) exhibited significant phenotypes, including dwarfism, high PPi concentrations, ectopic starch accumulation, decreased cellulose and callose levels, and structural cell wall defects. Altered cell arrangements and weakened cell walls in the root tip were particularly evident in fugu5 ppa1 and were more severe than in fugu5 . Our results indicate that H + -PPase is essential for maintaining adequate PPi levels and that the cytosolic PPa isozymes, particularly PPa1, prevent increases in PPi concentrations to toxic levels. We discuss fugu5 ppa1 phenotypes in relation to metabolic reactions and PPi homeostasis.